Nasal septum extramedullary plasmacytoma - Belić Branislav; Mitrović Slobodanka; Arsenijević Snežana; Erdevički Ljiljana; Stojanović Jasmina; Stojanović Stevan; Stolić Radojica (Vojnosanitetski Pregled)
Introduction. Plasmacytomas are malignant tumors characterized by abnormal monoclonal proliferation of plasma cells. They originate in either bone - solitary osseous plasmacytoma, or in soft tissue - extramedullary plasmacytoma (EMP). EMP represents less than 1% of all head and neck malignancies. Case report. We presented a case of EMP of the nasal septum in a 44-year-old male who had progressive difficulty in breathing through the nose and frequent heavy epistaxis on the right side. Nasal endoscopy showed dark red, soft, polypoid tumor in the last third of the right nasal cavity arising from the nasal septum. The biopsy showed that it was plasmacytoma. Bence Jones protein in the urine, serum electrophoresis, bone marrow biopsy, skeletal survey and other screening tests failed to detect multiple myeloma. This confirmed the diagnosis of EMP. The mass was completely removed via an endoscopic approach, and then, 4 week later, radiotherapy was conducted with a radiation dose of 50 Gray. No recurrence was noted in a 3-year follow- up period. Conclusion. EMP of the nasal cavity, being rare and having long natural history, represents a diagnostic and therapeutic challenge for any ear, nose and throat surgeon. Depending on the resectability of the lesion, a combined therapy is the accepted treatment.